The SOCO Scale: A Measure of the Customer Orientation of Salespeople - Saxe, Robert; Weitz, Barton A. (Journal of Marketing Research, 1982)
The concept of customer orientation in salespeople is defined, a scale is developed to measure the degree to which salespeople engage in customer-oriented selling, and the properties of the scale are reported. A test of the nomological validity indicates the use of customer-oriented selling is related to the ability of the salespeople to help their customers and the quality of the customer-salesperson relationship.